Prophetic Representations of the Divine Presence The Theological Interpretation of the Elijah-Elisha Cycles - Lunn, Nicholas P. (2015)
The narratives concerning Elijah and Elisha contain a number of unique elements, the most evident of which is the miracles they performed, without parallel among the other prophets. This article focuses on a further uniqueness hitherto undetected in scholarly research. Many of the episodes involving Elijah and Elisha include language relating either to the Hebrew sanctuaries, namely, the tabernacle and temple, or to theophanies. These two are conceptually associated in that both serve as representations of the divine presence. Allusions to the ritual and furniture of the sanctuary, as well as theophanic elements centering on the prophets, are taken as deliberate literary devices intended to communicate a message to the people of Israel. The latter part of this article discusses the theological import of this message, primarily within its immediate historical context, but also within the larger canonical framework.
Keywords: Theology; Theophany; Altars; Chariots; Divination; Divine Presence; Divinity; Prophets; Tabernacles; Temples